Relationships between kinematics and undulatory underwater swimming performance - Higgs, A. J.; Pease, D. L.; Sanders, R. H. (Journal of Sports Sciences, 2017)
Undulatory underwater swimming (UUS) is one of the major skills contributing to performance in competitive swimming. UUS has two phases- the upbeat is performed by hip extension and knee flexion, and the downbeat is the converse action. The purpose of this study was to determine which kinematic variables of the upbeat and downbeat are associated with prone UUS performance in an elite sample. Ten elite participants were filmed performing three prone 20 m UUS trials. Seven landmarks were manually digitised to calculate eighteen kinematic variables, plus the performance variable- horizontal centre of mass velocity (VCOM). Mean VCOM was significantly correlated with body wave velocity (upbeat r = 0.81, downbeat r = 0.72), vertical toe velocity (upbeat r = 0.71, downbeat r = 0.86), phase duration (upbeat r = -0.79), peak hip angular velocity (upbeat r = 0.73) and mean knee angular velocity (upbeat r = -0.63), all significant at P < 0.05. A multiple stepwise regression model explained 78% of variance in mean VCOM. Peak toe velocity explained 72% of the variance, and mean body wave velocity explained an additional 6%. Elite swimmers should strive for a high peak toe velocity and a fast caudal transfer of momentum to optimise underwater undulatory swimming performance.